Pelatihan Manajemen Perawatan Diri untuk Meningkatkan Pengetahuan Keluarga dan Pasien Gagal Jantung - Beti Kristinawati; Fahrun Nur Rosyid; Ardhu Rizkiawan; Laila Shofiya (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Heart failure is the most common cardiovascular disease and has an uncontrolled prevalence of risk factors. Self-care management is the ability of heart failure patients to manage themselves and their illness. Based on the assessment data at the service site, there were as many as 30 heart failure patients and 30 families with heart failure patients. This service aims to improve the knowledge and skills of families and patients with heart failure in carrying out self-management. This service was carried out in one of the health cadre's houses which was attended by 30 people with heart disease. Powerpoint media is used as a medium for counseling activities delivered verbally by the speaker within 45 minutes after evaluation is carried out with redemostration. The results showed that 90% of respondents understood the material provided, this can be seen from the response to questions and the desire of the family and patients to practice again after the simulation at the evaluation time. Self-care management can be improved by education and training through simulations. Good self-management in people with heart failure is associated with a reduced risk of death and re-hospitalization events. Conducting supportive education and training to improve self-care behaviors in heart failure patients can improve knowledge, skills, reduce symptoms, and reduce patient complaints.